2015
DOI: 10.1007/s00427-015-0505-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression study of the hunchback ortholog in embryos of the onychophoran Euperipatoides rowelli

Abstract: Zinc finger transcription factors encoded by hunchback homologs play different roles in arthropods, including maternally mediated control, segmentation, and mesoderm and neural development. Knockdown experiments in spider and insect embryos have also revealed homeotic effects and gap phenotypes, the latter indicating a function of hunchback as a "gap gene". Although the expression pattern of hunchback has been analysed in representatives of all four major arthropod groups (chelicerates, myriapods, crustaceans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The behavior of the Pt-Ets4 positive cells is reminiscent of migrating gastrulating cells that invade the germ-disc from the center and from the rim of the germ-disc ( Mittmann and Wolff, 2012 ; Kanayama et al, 2011 ; Yamazaki et al, 2005 ) (see Video 1A ). As Pt-Ets4 activates the expression of Pt-hb (a gene that is known to be expressed in mesodermal cells in diverse animals [ Schwager et al, 2009 ; Franke and Mayer, 2015 ; Kerner et al, 2006 ]) we wondered if Pt-Ets4 misexpression is inducing a mesoderm-like cell fate. For this reason, we tested whether the ectopic expression of Pt-Ets4 is also inducing the expression of the key mesodermal marker Pt-twist ( Pt-twi ).…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of the Pt-Ets4 positive cells is reminiscent of migrating gastrulating cells that invade the germ-disc from the center and from the rim of the germ-disc ( Mittmann and Wolff, 2012 ; Kanayama et al, 2011 ; Yamazaki et al, 2005 ) (see Video 1A ). As Pt-Ets4 activates the expression of Pt-hb (a gene that is known to be expressed in mesodermal cells in diverse animals [ Schwager et al, 2009 ; Franke and Mayer, 2015 ; Kerner et al, 2006 ]) we wondered if Pt-Ets4 misexpression is inducing a mesoderm-like cell fate. For this reason, we tested whether the ectopic expression of Pt-Ets4 is also inducing the expression of the key mesodermal marker Pt-twist ( Pt-twi ).…”
Section: Resultsmentioning
confidence: 99%
“…RNA isolation and cDNA synthesis were performed as described previously [ 11 , 55 , 138 ]. Fragments of NK1 , NK3 , NK4 , NK5 , NK6 , Msx , Lbx and Tlx were amplified from the cDNA using specific primers (Table 3 ) and Phusion Green High-Fidelity DNA Polymerase (2 U/µl; Thermo Scientific, Waltham, MA, USA) to obtain PCR fragments with blunt ends.…”
Section: Methodsmentioning
confidence: 99%
“…Directly developing onychophorans (Figure S3B) possess serial, ciliated metanephridia in each trunk segment (Figure 3D), which develop directly from the mesodermal rudiment at the base of each leg and, unlike the metanephridia of spiralians, are not preceded by any larval organs. 39 Expression of some of the candidate nephridial genes has been already investigated in onychophorans and showed that osr and lhx1/5 are indeed expressed in the metanephridial rudiments, 40,41 while hunchback does not seem to be directly involved in nephridiogenesis 42 (however, it is expressed in the limb mesoderm, which might include some progenitor cells giving rise to the metanephridia). 39 Three of the remaining TFs (eya, six1/2, and pou3) are expressed in the developing metanephridia associated with the walking appendages (Figures 4D and S3C).…”
Section: Molecular Development Of Uf-based Organs In Ecdysozoamentioning
confidence: 99%